Salivary extracellular vesicles inhibit Zika virus but not SARS‐CoV‐2 infection. Issue 1 (24th August 2020) - Conzelmann, Carina; Groß, Rüdiger; Zou, Min; Krüger, Franziska; Görgens, André; Gustafsson, Manuela O; El Andaloussi, Samir; Münch, Jan; Müller, Janis A.
ABSTRACT: Zika virus (ZIKV) is mainly transmitted via mosquitos, but human‐to‐human transmissions also occur. The virus is shed into various body fluids including saliva, which represents a possible source of viral transmission. Thus, we here explored whether human saliva affects ZIKV infectivity. We found that physiological concentrations of pooled saliva dose‐dependently inhibit ZIKV infection of monkey and human cells by preventing viral attachment to target cells. The anti‐ZIKV activity in saliva could not be abrogated by boiling, suggesting the antiviral factor is not a protein. Instead, we found that purified extracellular vesicles (EVs) from saliva inhibit ZIKV infection. Salivary EVs (saEVs) express typical EV markers such as tetraspanins CD9, CD63 and CD81 and prevent ZIKV attachment to and infection of target cells at concentrations that are naturally present in saliva. The anti‐ZIKV activity of saliva is conserved but the magnitude of inhibition varies between individual donors. In contrast to ZIKV, severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2), predominantly spreading via respiratory droplets, is not affected by saliva or saEVs. Our findings provide a plausible explanation for why ZIKV transmission via saliva, i.e. by deep kissing have not been recorded and establish a novel oral innate immune defence mechanism against some viral pathogens.